A case of mirror image agnosia and mirrored self-misidentification syndrome in schizophrenia without dementia or structural abnormalities. Issue 5 (2nd September 2020) - Rong, Carola; Issac, Aaron Gerard; Alkan, Elif Sena; Fashina, Oluwafunmibi; Ding, Karen; Selek, Salih
ABSTRACT: Delusional misidentification syndrome (DMS) is an umbrella term encompassing a variety of disorders. One rare form of DMS is the delusional misidentification of one's own reflection, known as "mirrored self-misidentification syndrome". In "mirror image agnosia", the ability to identify the image of self and/or others in the mirror is lost, while the ability to identify the mirror itself is preserved. To our knowledge, mirror image agnosia has never been described in a patient with schizophrenia. Herein we present a case of a patient with schizophrenia with severe delusions of both mirrored self-misidentification and mirror image agnosia without any structural abnormalities or dementia.